2015
DOI: 10.1071/ah14119
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care health professionals’ experiences of caring for patients with advance care directives

Abstract: Objective. To explore the health professionals' (HPs) perceptions and experiences of advance care directives (ACDs) and advance care planning in Australian palliative care services.Methods. A nationwide survey of 105 palliative care services was conducted, with two HPs from each service invited to participate. A qualitative analysis of open responses about advance care planning was undertaken.Results. Sixty questionnaires were returned with open responses. Most responders were nurses (75%), aged 40 years (80%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
2
17
0
7
Order By: Relevance
“…Additionally, an Australian study constituted a more positive approach to AD and its application in emergency cases, and AD was regarded as the appropriate instrument to reduce tension and manage potential conflicts among patients, family members and health professionals [27]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an Australian study constituted a more positive approach to AD and its application in emergency cases, and AD was regarded as the appropriate instrument to reduce tension and manage potential conflicts among patients, family members and health professionals [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Some of the nursing personnel claimed such a responsibility is not a part of their competence and consequently they would prefer not to take it upon themselves to discuss this with their patients [27]. Meanwhile, some studies claim AD should be part of nurses’ practice, but it should not be a priority when caring for patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…As over 50% of Australians die in hospitals, policy and standards encourage hospitals to support ACP [1][2][3][4][5] to improve the quality of end-of-life (EOL) care. [6][7][8][9][10] However, a 2014 review found that ACP documentation is often limited, inaccessible and not associated with improved care quality. Health care improvement organisations advocate that hospitals develop systems to elicit, store and act on patient preferences in a dependable way.…”
Section: Outline Of Problemmentioning
confidence: 99%
“…Mūsų tyrimo duomenys gana panašūs ir rodo, kad tik šiek tiek daugiau nei pusė visų respondentų tiki, kad tai padėtų išspręsti moralinės atsakomybės pasiskirstymo klausimą tarp sveikatos priežiūros profesionalo ir paciento. Lyginant su panašaus pobūdžio tyrimais, šiame taip pat nustatyta, kad vis daugiau sveikatos priežiūros specialistų pripažįsta, kad gyvenimo pabaigos klausimų svarstymas iš anksto su pacientais yra jiems etiškai priimtinas, tačiau nėra aiškus pacientų požiūris [18,19].…”
Section: Rezultatų Aptarimasunclassified